FUSION OF FACE, FINGER PRINT & IRIS FEATURES FOR BIOMERTIC AUTHENTICATION SYSTEM - Navjeet Kaur, Karamjeet Singh (International Journal of Research Science and Management, 2015)
Now these days, biometrics gaining more importance because of recognition system. In this paper, we discuss about eye, face and fingerprint recognition. Images of all three are normalized and features are extracted. Then fusion is done. We classified the distance by database. Then recognition is done and evaluates the parameters.